2008
DOI: 10.1097/mot.0b013e3282f63942
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas preservation for pancreas and islet transplantation

Abstract: Purpose of review-To summarize advances and limitations in pancreas procurement and preservation for pancreas and islet transplantation, and review advances in islet protection and preservation.Recent findings-Pancreases procured after cardiac death, with in-situ regional organ cooling, have been successfully used for islet transplantation. Colloid-free Celsior and histidinetryptophan-ketoglutarate preservation solutions are comparable to University of Wisconsin solution when used for cold storage before pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 71 publications
0
35
0
1
Order By: Relevance
“…Existing protocols for maintaining human islets in vitro are limited, allowing only short-term (less than 72 h) storage of cells under conventional static culture conditions [5]. Extending the duration of culture beyond this period usually results in a significant loss of structural integrity within the islets and a decline in glucose-stimulated insulin release [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Existing protocols for maintaining human islets in vitro are limited, allowing only short-term (less than 72 h) storage of cells under conventional static culture conditions [5]. Extending the duration of culture beyond this period usually results in a significant loss of structural integrity within the islets and a decline in glucose-stimulated insulin release [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…[87][88][89] There were some early attempts in the 1970s to develop a protocol with MP and low perfusion pressures, but until recently, MP has been out of favor, as results from some early experiments favored cold storage, which was comparably straightforward. 90 Islet yields and quality have improved with the innovation of cold preservation techniques by the use of a 2-layer method that is now widely used in transplant centers, although it has been suggested that MP may further improve yields. 90 There are few recent studies involving ICT and MP for preservation, and even fewer with whole pancreas transplant.…”
Section: Machine Perfusionmentioning
confidence: 99%
“…For the latest progress in these aspects of islet transplantation, readers are referred to two recently published review articles [8,9] .…”
Section: Great Efforts To Optimize Islet Transplantationmentioning
confidence: 99%